Multivariate analysis of growth and yield traits of aman rice genotypes in Barishal region of Bangladesh - Nazmun Nahar; Khadiza Khatun; Nazmul Alam Khan; Md Rafiqul Islam; Mossammot Moriom; Nusrat Jahan; Shamim Akram; Muhammad Maruf Husain (Research in Agriculture Livestock and Fisheries, 2025)
Rice (Oryza sativa L.) is the most important staple crop worldwide in terms of production and cultivation area. In rice breeding efforts, the degree of genetic diversity is a significant factor in selecting appropriate genotypes. This study was carried out to determine genetic diversity among fifteen rice genotypes by assessing different morphological yield traits using multivariate analysis. Our results record significant variation with considerable values for certain specific traits for certain genotypes, indicating genetic diversity among the genotypes. Cluster analysis categorized genotypes into four clusters based on growth and yield characteristics. Significant variations were observed in plant height, panicle length, number of effective tillers per plant, and grain yield. The highest yielding rice genotype was IR18A1075 (6.35 t/ha), followed by IR17A1633 (6.31 t/ha). The maximum distance (43.74) was identified between cluster centroids in cluster III and cluster IV, showing genetic dissimilarity among genotypes that can be used in hybrid breeding programs. Cluster II genotypes exhibited the maximum grain yield potential (5.52 t/ha), indicating the possible usefulness of these genotypes for rice improvement purposes, and it could be cultivated for increased grain yield. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 353-362